2001
DOI: 10.1097/00125817-200107000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Packed red cell transfusion does not compromise chromosome analysis in newborns

Abstract: Purpose: Critically ill neonates are frequently transfused with packed red cells. Some of these transfused neonates also need chromosome analysis. There is a long-standing tradition in pediatrics of not performing chromosome analysis after transfusion. We wished to determine whether transfusion with packed red cells affect the cytogenetic results in neonates. Method: The medical records of all neonates at the Medical College of Georgia who had had chromosome analysis between June 1995 and June 1998 were review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…In a retrospective study, Kulharya et al 8 reviewed the medical records of 10 newborn infants who had received blood transfusions between 1 to 10 days before routine cytogenetic analysis. Three infants received irradiated and leukodepleted blood, four infants received irradiated blood, and three infants received blood that was neither irradiated nor leukodepleted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study, Kulharya et al 8 reviewed the medical records of 10 newborn infants who had received blood transfusions between 1 to 10 days before routine cytogenetic analysis. Three infants received irradiated and leukodepleted blood, four infants received irradiated blood, and three infants received blood that was neither irradiated nor leukodepleted.…”
Section: Discussionmentioning
confidence: 99%
“…Because there were no instances where cells with a karyotype of the opposite sex were detected in the neonates' blood samples, the authors concluded PRBC transfusions did not compromise the accuracy of chromosome analysis. 8 Because this study was retrospective, there was no documentation on which patients received blood from opposite sex donors. The authors concluded that the likelihood of study patients receiving blood from a donor of the opposite sex was 50% based on the 1:1 male to female donor ratio in the blood bank.…”
Section: Discussionmentioning
confidence: 99%
“…Initially focusing on transfusion-related acute lung injury (TRALI) following plasma and platelet transfusion from a female donor, recent observational studies have also highlighted similarly increased mortality in transfusion recipients of RBCs from female donors [ 26 , 27 , 28 ]. While the effects of donor characteristics, including donor sex, on transfusion outcomes has been systematically reviewed [ 29 ], this meta-analysis of all patient groups included only two studies in newborns [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In studies of cytogenetic testing following of irradiated, leukodepleted, packed red blood cells, no donor chromosomes were found in downstream analysis, suggesting that there is limited evidence to support delaying genetic testing following transfusion. 15,16 •…”
mentioning
confidence: 99%